PENGARUH POTONGAN HARGA, E-SERVICE QUALITY DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SHOPEEFOOD MAHASISWA UDINUS - ARIANTI, RISMA; Chasanah, Amalia Nur (Fakultas Ekonomi Universitas Wisnuwardhana, 2024)
In the modern era driven by technology, food delivery services have experienced rapid development as a solution to meet the food needs of increasingly busy consumers. The sample determination was carried out using the Lemeshow formula with a sample size of 100. Researchers applied a non-probability sampling method using purposive sampling technique in this study. The type of research conducted is explanatory with a quantitative approach. The location of this research is in Semarang City, Central Java. The calculation results show that: 1. That Rebates, E-Service Quality, and Promotion simultaneously influence ShopeeFood consumer purchasing decisions. 2. That Partial Discounts do not have a significant effect on discounted prices on purchasing decisions. 3. That E-Service Quality partially has a significant influence on shopeefood consumer purchasing decisions. 4. That Promotion partially has a significant influence on shopeefood consumer purchasing decisions.